2007
DOI: 10.1007/s00415-006-0409-3
|View full text |Cite
|
Sign up to set email alerts
|

Brain responses to emotional stimuli in patients with amyotrophic lateral sclerosis (ALS)

Abstract: Amyotrophic lateral sclerosis (ALS), a progressive motor neuron disease, affects movement and communication abilities and emotional processing. Subjective ratings of emotional stimuli depicting social interactions and facial expressions differed significantly between ALS patients and healthy controls in a previous study with a reduction of negative emotional valence (pleasantness) and lower subjective arousal (excitement) in ALS patients. In the present study, sixty similar emotional slides were presented to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
62
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 35 publications
8
62
0
3
Order By: Relevance
“…Papps et al [16] found a selective failure in memory for emotional material in ALS, while Lulé et al [17] found altered emotional responses to a picture test with respect to positive valence and decreased excitability for extremely emotional stimuli. In a more recent fMRI study, the same authors [18] found that ALS patients showed increased activation in the right supramarginal area and a reduced response in extrastriate visual areas when presented with emotional stimuli depicting social interaction and facial expression. Thus, compared to healthy controls, ALS patients showed enhanced (i.e.…”
Section: Introductionmentioning
confidence: 90%
“…Papps et al [16] found a selective failure in memory for emotional material in ALS, while Lulé et al [17] found altered emotional responses to a picture test with respect to positive valence and decreased excitability for extremely emotional stimuli. In a more recent fMRI study, the same authors [18] found that ALS patients showed increased activation in the right supramarginal area and a reduced response in extrastriate visual areas when presented with emotional stimuli depicting social interaction and facial expression. Thus, compared to healthy controls, ALS patients showed enhanced (i.e.…”
Section: Introductionmentioning
confidence: 90%
“…94 Functional cortical changes have been observed in patients with ALS without cognitive/behavioral impairment during processing of socioemotional stimuli (ie, pictures of persons in emotional situations). 95 Compared with controls, patients with ALS showed an increased activation of the right supramarginal gyrus. 95 …”
Section: 93mentioning
confidence: 96%
“…95 Compared with controls, patients with ALS showed an increased activation of the right supramarginal gyrus. 95 …”
Section: 93mentioning
confidence: 96%
“…Un estudio con RM funcional demostró una mayor activación en el giro supramarginal derecho en pacientes con una sensibilidad alterada a claves sociales y emocionales 83,84 . También se han reportado déficits en la Teoría de la Mente y detección del sarcasmo 77,85,86 .…”
Section: Procesamiento Emocional Y Cognición Socialunclassified